Caspase 3 exhibits a yeast metacaspase proteostasis function that protects mitochondria from toxic TDP43 aggregates - Steve Brunette; Anupam Sharma; Ryan Bell; Lawrence Puente; Lynn A Megeney (Microbial Cell, 2023)
Caspase 3 activation is a hallmark of cell death and there is a strong correlation between elevated protease activity and evolving pathology in neurodegenerative disease, such as amyotrophic lateral sclerosis (ALS). At the cellular level, ALS is characterized by protein aggregates and inclusions, comprising the RNA binding protein TDP-43, which are hypothesized to trigger pathogenic activation of caspase 3. However, a growing body of evidence indicates this protease is essential for ensuring cell viability during growth, differentiation and adaptation to stress. Here, we explored whether caspase 3 acts to disperse toxic protein aggregates, a proteostasis activity first ascribed to the distantly related yeast metacaspase ScMCA1. We demonstrate that human caspase 3 can functionally substitute for the ScMCA1 and limit protein aggregation in yeast, including TDP-43 inclusions. Proteomic analysis revealed that disrupting caspase 3 in the same yeast substitution model resulted in detrimental TDP-43/mitochondrial protein associations. Similarly, suppression of caspase 3, in either murine or human skeletal muscle cells, led to accumulation of TDP-43 aggregates and impaired mitochondrial function. These results suggest that caspase 3 is not inherently pathogenic, but may act as a compensatory proteostasis factor, to limit TDP-43 protein inclusions and protect organelle function in aggregation related degenerative disease.